Misurare la leadership responsabile degli studenti e degli scout utilizzando modelli di regressione lineare - Émiliane Rubat du Mérac (LED Edizioni Universitarie, 2014)
Evaluating Value-based Leadership of Students and Scouts Using Linear Regression Models) The study aims to evaluate the impact of some aspects of two educational contexts, school and Scouting, on the development of adolescent leadership attitudes. The research instruments are: the Educational Context Perception Questionnaire (ECPQ), designed to identify the characteristics of the two educational settings through adolescents' perceptions, and the Socially Responsible Leadership Scale (SRLS), adapted to the Italian context, to measure their value-based leadership attitudes. The questionnaires were submitted to a judgment sample of 600 students and 231 Scouts enrolled in upper secondary schools in Rome (9th and 10th grades). The ECPQ was also administered to 34 teachers and 64 scout leaders. One-way ANOVA and the post-hoc Bonferroni test were used to analyze group differences based on role (teacher/student), school type and educational context (school/scouting). The association between the ECPQ and Leadership scales was evaluated by multiple linear regression. The data indicate that the quality of the interactions and the way in which power and responsibilities are shared within the class have a significant impact on the development of the students' value-based leadership. Furthermore, the teachers' data suggest the hypothesis of an impact of their school perception on the students' perception of their classroom.